The aplication of teleradiology in dentomaxillofacial radiology - Fahmi Oscandar; Yurika A. Lita; Farina Pramanik (Journal of Dentomaxillofacial Science, 2016)
Radiograph interpretation which is conducted by dentomaxillofacial radiologist has a problem with distance, time and limited number of dental radiologist in Indonesia that it becomes an obstacles to provided expansive and be spread evently radiograph interpretation services. The objective of this review to provide information to general dentist and other dental specialist about teleradiology advantage in dentomaxillofacial radiology as comunication media between dental radiologist and other dental specialist using teleradiology system. Radiographs imaging can be easily sent from dental radiologist to other dental spesialist not only in the sections of the hospital but also other locations throughout the world. The teleradiology system need adequate internet capacity, internet speed and bandwith. Benefits of using teleradiology is able to achieve efectivity dentomaxillofacial radiology services. As conclusion, teleradiology can be used as communication media between dentomaxillofacial radiologist with other dental specialists, especially in providing services radiograph interpretation thus can provide patient services effectively and efficiently, without problem of human resources, time, distance and location.